Growth and Persistence of Large Business Groups in India - Rajakumar, J.; Henley, John (Journal of Comparative International Management, 2007)
The international business literature is belatedly recognizing the significance of large family-controlled business groups in emerging markets. Most research has focused on analyzing the impact of concentrations of private wealth on economic development in home countries using panel data. This paper examines the growth and persistence of business groups since 1951 in one country – India. Since Independence, the government has attempted to operate an economic policy framework that had, amongst its prime objectives, the curbing of the tendency of business groups to concentrate economic power. As their growth was seen as synonymous with concentration of wealth, business groups became obvious candidates for regulation. Various policy instruments were introduced, such as the Industries (Development and Regulation) (IDR) Act 1951 and the Monopolies and Restrictive Trade Practices (MRTP) Act 1969, with the aim of erecting barriers to their growth. In 1991, economic reform ushered in the removal of the legislative barriers to business group growth. The analysis in this paper concludes that large business groups expanded their share of wealth between 1951 and 1969, but this growth was arrested between 1970 and 1990, and since 1991, it has dwindled. The pre-eminent position of Tata and Birla, as the two largest business groups, remained unchallenged from 1951 until the emergence of the Reliance Group in the late 1990s. However, there has been frequent change in the relative positions of other groups in and out of the Top-20. After economic liberalisation accelerated from 1991, there was significant change in the ranks of business groups in the Top-20. Existing smaller groups or newly emerging groups, particularly in the IT and telecommunications sectors, have replaced many of the previously dominant older groups. This is interpreted as indicating the central role of entrepreneurship in combination with technological innovation, and the opening up of the Indian economy to international competition, in disturbing established business hierarchies in India. More generally, policy intervention appears to have been less effective in breaking up concentrations of economic power in India than economic liberalization and increased competition.